2010
DOI: 10.1021/jf102812t
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Regulates Inflammatory Mediator Expression through Modulating NF-κB, Mitogen-Activated Protein Kinases, Protein Kinase C, and Reactive Oxygen Species

Abstract: Osthole, a coumarin compound, has been reported to exhibit various biological activities; however the cellular mechanism of its immune modulating activity has not yet been fully addressed. In this study we isolated osthole from the seeds of Cnidium monnieri and demonstrated that osthole inhibited TNF-α, NO and COX-2 expression in LPS-stimulated macrophages, without reducing the expression of IL-6. Furthermore, the phosphorylation of p38, JNK1/2, PKC-α and PKC-ε induced by LPS was inhibited by osthole; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 30 publications
(55 reference statements)
9
95
0
Order By: Relevance
“…In contrast, p38 MAPK inhibitors attenuate renal damage by reducing inflammatory mediator production [23]. Osthole is reported to abrogate p38 MAPK activation in LPS-stimulated macrophages [24]. Consistent with that report, the present data showed that osthole treatment attenuates p38 MAPK activation, contributing to ameliorating the inflammatory response in injured kidneys.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, p38 MAPK inhibitors attenuate renal damage by reducing inflammatory mediator production [23]. Osthole is reported to abrogate p38 MAPK activation in LPS-stimulated macrophages [24]. Consistent with that report, the present data showed that osthole treatment attenuates p38 MAPK activation, contributing to ameliorating the inflammatory response in injured kidneys.…”
Section: Discussionsupporting
confidence: 81%
“…Another natural coumarin, osthole, which has immunomodulatory activities, also inhibits COX-2 expression in LPS-stimulated macrophages. 26) Our observation that 4-methylcoumarin derivatives reduce COX-2 and iNOS expression is in line with the above mentioned investigation that show the target of these compounds is at the protein expression level.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that various coumarin derivatives are able to inhibit LPS-induced NO 10,25,26) and PGE 2 production 10) in macrophages and other investigators have reported the ability of coumarin related compounds in lowering the protein expression of inflammatory enzymes. It has been observed that 7,8-diacetoxy-4-methylcoumarin reduces COX-2 expression in A549 human lung adenocarcinoma cells 27) and other authors, studying the effect of 63 natural oxycoumarin derivatives on LPS-induced inflammation in RAW264.7 cells, showed that many of these compounds inhibited the protein expressions of iNOS and COX-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously isolated osthol from C. monnieri fruits and reported antifibrotic activity (Shin et al, 2011). Diverse biological activity of osthol including antitumor, anti-inflammatory, and neuroprotective activities have been also reported (Chao et al, 2014;Chou et al, 2007;Liao et al, 2010;Liu et al, 2010). In the present study, we investigated the melanogenesis inhibitory activity of osthol in B16F10 melanoma cells.…”
Section: Introductionmentioning
confidence: 99%